PENGARUH LOKASI, HARGA, DAN KEBERAGAMAN PRODUK TERHADAP MINAT BELI PADA PASAR TRADISIONAL KIRINGAN - Luluk Nur Azizah (Media Mahardhika, 2020)
The lower the number of people interested in going to traditional markets, modern markets are starting to enter the city area, the shops are so dense that the competition is getting tougher, it also makes people as consumers reconsider their buying interest in the Kiringan market. This study aims to determine: (1) the effect of location, price, and product variation on buying interest in the Kiringan traditional market. (2) the effect of location on buying interest in the Kiringan traditional market, (3) the effect of price on the buying interest in the Kiringan traditional market, and (4) the effect of product variation on the buying interest in the Kiringan traditional market from Kiringan. This research is a survey research design using associative research methods. The research population is customers in Kiringan traditional market. numbering 200 people. Data were collected using tested validity and reliability questionnaires. Data were analyzed using multiple regression analysis techniques. The results showed that: (1) location, price, and product variation had a positive effect on buying interest in the Kiringan traditional market. This is evidenced by the calculated F value of 65.014 with a significance of 0.000 <0.05; (2) location has a positive effect on buying interest in the Kiringan traditional market. This is evidenced by the t-count value of 3,968 with a significance value of 0,000 <0.05 and a regression coefficient of 0.195; (3) price has a positive effect on buying interest in Kiringan traditional market. This is evidenced by the t value of 5.164 with a significance value of 0.000 <0.05 and a regression coefficient of 0.310; and (4) product variation has a positive effect on buying interest in Kiringan traditional market. This is evidenced by the t value of 6.548 with a significance value of 0.000 <0.05 and a regression coefficient of 0.359.